Visualizing victory - Investigating an immersive VR game analysis tool for badminton - Dänekas, B.; Zargham, N.; Zhang, S.; Vajen, R.; Bhattacharjee, S.; Khadse, S.; Loerakker, M. B.; Malaka, R. (15. Symposium der dvs-Sektion "Sportinformatik und Sporttechnologie": Zwischen Geistesakrobatik und praktischer Anwendung: Innovationen in der Sportinformatik und Sporttechnologie, 2024)
Introduction Technology has enhanced sports performance and our understanding of sports dynamics. A prominent application of technology in this domain is gameplay analysis, which enables detailed review and evaluation of athletes' performances. This analytical approach allows athletes to reflect on their actions, pinpoint strengths and weaknesses, and make informed adjustments to their training and future performances. This process is especially crucial in team sports, where tactics and spatial strategies are key. The rise of virtual reality (VR) has introduced more immersive methods for performance analysis. In this work, we investigate an immersive analysis tool for badminton called VIRD (Lin et al., 2023), leveraging VR to enable trainers and players to review their performance comprehensively. Badminton, a fast-paced and widely popular sport, presents unique challenges due to its rapid tempo, making traditional observation inadequate for fully understanding game situations (Manrique et al., 2003). An immersive VR tool could provide a more comprehensive and dynamic analysis.